'Attending to the wound and the person' – patients' experiences and expectations of a newly established traumatic brain injury clinic. (6th December 2017) - Mueller, Christoph; Wang, Yuepeng; Brooks, Alice; Morant, Nicola; Sullivan, Paul; Raymont, Vanessa
ABSTRACT: Primary objective : This qualitative study aimed to gain a better understanding of how medical and social services in the UK currently support patients with Traumatic Brain Injury (TBI) in the community. Furthermore, we explored patients' wishes and expectations of a newly established TBI clinic. Methods and procedures : We conducted semi-structured interviews with 10 patients with mild-to-severe TBI. The interview schedule was designed to cover contacts with health services, information provided, post-discharge support, current social circumstances, expectations from the newly established brain injury service and participants' desires for any new service. Transcripts were analysed using a thematic analysis. Main results : Participants highlighted the importance of the human component of their care and of fostering trusting relationships. This validates patients' experience and helps them to regain confidence. Follow-up and education are important for patients and relatives through all stages of care, regardless of the severity of the injury. Patients strive for meaningful lives and need to be supported to engage in activities. They need hands-on support, particularly with the UK's bureaucratic welfare system. Conclusions : There is much room for improvement in the TBI community care in the UK. Our findings support the development of a holistic service that can address the multifactorial problems which the patients with TBI and their families face.